How can I solve `x^2 - (1 + I)*x + 6 + 3*I == 0`

to get answers z = 3*I and z = 1 - 2*I? When I enter
solve(x^2 - (1 + I)*x + 6 + 3*I == 0, x)
I get
[x == -1/2*sqrt(-10*I - 24) + 1/2*I + 1/2, x == 1/2*sqrt(-10*I - 24) + 1/2*I + 1/2]

1 | initial version |

How can I solve `x^2 - (1 + I)*x + 6 + 3*I == 0`

to get answers z = 3*I and z = 1 - 2*I? When I enter
solve(x^2 - (1 + I)*x + 6 + 3*I == 0, x)
I get
[x == -1/2*sqrt(-10*I - 24) + 1/2*I + 1/2, x == 1/2*sqrt(-10*I - 24) + 1/2*I + 1/2]

How can I solve `x^2 - (1 + I)*x + 6 + 3*I == 0`

to get answers `z = `

~~3~~*I **3*I** and z = 1 - *

`I? 2*I`

? When I `solve(x^2 - (1 + `~~I)~~*x **I)*x + 6 + *~~3~~I 3*I == 0, x)

I ~~get
~~get

`[x == `~~-1/2~~*sqrt(-10*I -1/2*sqrt(-10*I - 24) + ~~1/2~~*I **1/2*I + 1/2, x == *~~1/2~~sqrt(-10*I 1/2*sqrt(-10*I - 24) + *~~1/2~~I 1/2*I + ~~1/2]~~1/2]

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.